Belterra em verso: análise do poema “O Duelo Sangrento” de Francisco Bezerra - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2025)
This article consists of developing an analysis of the poem “O Duelo sangrento”, from a historical-cultural and academic point of view. Taking into account that the episode narrated throughout the poem presents readers with real facts that occurred in the city of Belterra, which is described by characteristics that mention its construction, in the same way that it qualifies the individuals residing in the municipality, as well as local agriculture. Furthermore, for a poem analysis there is a need to know the elements that make up a poem, that being said, the analysis defines the type of poem, stanzas and verses. Therefore, the objectives of this research are to understand the history of the city that follows the event, as well as to find out about the literary genre in which the work is inserted, through research methodology based on the deductive method throughout the outlined study, which aims to review research literature.
Keywords: Belterra; Poema; Verso; CNPQ:: LINGÜÍSTICA, LETRAS E ARTE